Customer Relations in the Transportation Industry during Pandemic (Netnography Study on Instagram @kai121) - Fitri, Alifa Nur; Indrayani, Heni (Jurnal The Messenger, 2023)
Introduction: On restrictions during the pandemic, significantly reducing passenger numbers. PT KAI adapted by introducing innovations like Genose testing, online ticketing, and vaccination services to ensure safety and compliance. This paper examines PT KAI’s customer relations via Instagram (@kai121) during the pandemic. It focuses on using digital public relations and the SMART Relationship Management Process Model to maintain engagement and satisfaction. These efforts highlight KAI’s adaptability in meeting customer needs. Methods: This research employs Virtual Ethnography to observe interactions on 427 KAI posts made between March 2020 and October 2021. The data is then analyzed using Customer Relationship Management theory, incorporating the stages of Scan, Map, Act, Roll Out, Track, and Stew. Findings: The study found that during the pandemic, KAI’s Instagram content focused on various topics: corporate events (13.81%), national transportation policies (15.45%), health protocols (11.07%), train service promotions (38.38%), railway education (13.38%), and giveaway content (7.96%). The content prominently highlighted KAI services such as Rail Express, schedule updates, rapid/antigen testing, and KAI Access. Posts related to transportation policies and health protocols received significant engagement, with transportation policy updates garnering the most comments as followers sought the latest travel information. KAI effectively utilized digital public relations through Instagram to engage with customers. Originality: This study is novel as it is the first in Indonesia to analyze KAI’s customer relations through digital public relations during the pandemic.